2020
DOI: 10.1002/elan.202060377
|View full text |Cite
|
Sign up to set email alerts
|

Design of Solid‐contact Ion‐selective Electrode with Graphene Transducer Layer for the Determination of Flavoxate Hydrochloride in Dosage Form and in Spiked Human Plasma

Abstract: Eco-friendly solid-contact ion selective electrode was fabricated and optimized for the determination of flavoxate hydrochloride in presence of its main metabolite. The process is based on carbon screen printed electrode and polyvinyl chloride polymeric sensing membrane. The first optimization step involved the ionophore selection through screening various ionophores, where calix[4]arene showed the highest affinity towards flavoxate. The second step, a graphene nanocomposite interlayer was employed as the ion-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 44 publications
0
22
0
Order By: Relevance
“…Sodium tetraphenyl borate (NaTPB), calix [4]arene (CX4), tetrahydrofuran (THF) and polyvinyl chloride (PVC) were obtained from Sigma-Aldrich (Steinheim, Germany). The 2-nitrophenyl octyl ether (2-NPOE) was acquired from Fluka Chemie GmbH, (St. Louis, MO, USA).…”
Section: Chemicals and Materialsmentioning
confidence: 99%
See 2 more Smart Citations
“…Sodium tetraphenyl borate (NaTPB), calix [4]arene (CX4), tetrahydrofuran (THF) and polyvinyl chloride (PVC) were obtained from Sigma-Aldrich (Steinheim, Germany). The 2-nitrophenyl octyl ether (2-NPOE) was acquired from Fluka Chemie GmbH, (St. Louis, MO, USA).…”
Section: Chemicals and Materialsmentioning
confidence: 99%
“…In a stoppered glass tube, 190 mg PVC was precisely blended with 10 mg sodium tetraphenylborate (NaTPB), 10 mg calix [4]arene (CX4) as ionophore and 0.4 mL of 2-NPOE. The homogenized mixture was then dissolved by shaking with 6 mL THF to get the appropriate liquid membranes.…”
Section: Fabrication and Calibration Of The Potentiometric Sensormentioning
confidence: 99%
See 1 more Smart Citation
“…The characteristics of the electrode showed that the ion-to-electron transduction and the potential stability were promoted [ 23 , 24 ]. Amr M. Mahmoud fabricated an eco-friendly solid-contact selective electrode with GR as an electron-ion exchanger for the determination of flavoxate hydrochloride; the prepared electrode showed little potential drift and good stability in comparison with the electrode without the graphene layer [ 25 ]. Surface groups were produced in the carbon-based nanomaterials by purification, carboxylation and chemical modification [ 22 , 25 , 26 , 27 , 28 ].…”
Section: Introductionmentioning
confidence: 99%
“…Amr M. Mahmoud fabricated an eco-friendly solid-contact selective electrode with GR as an electron-ion exchanger for the determination of flavoxate hydrochloride; the prepared electrode showed little potential drift and good stability in comparison with the electrode without the graphene layer [ 25 ]. Surface groups were produced in the carbon-based nanomaterials by purification, carboxylation and chemical modification [ 22 , 25 , 26 , 27 , 28 ]. The carboxylated and modified nanomaterials were suitable as substrates for reacting with specific ions, but the structural damage would reduce their mechanical properties.…”
Section: Introductionmentioning
confidence: 99%